The Impact of Trust, Perceived Usefulness, Perceived Ease of Use, and Customer Intentions on Customer Attitudes Toward the Use of Technology - Bustaman, Muhammad Khairil; Aprianingsih, Atik; Hidayat, Malvin; Dasuki, Rima Elya (Almana : Jurnal Manajemen dan Bisnis, 2023)
An online store must constantly innovate by developing new ideas or reusing established ones like the Cash on Delivery payment option. In this study, the author supposes that trust, perceived usefulness, and perceived ease of use can positively affect a customer's attitude toward adopting a technology, affecting their behavioral Intention to use the technology. Therefore, to demonstrate this, the author attempts to conduct research using the Technology Acceptance Model with the addition of trust as an external variable and analyzes them using Path Analysis tools to determine why the customers would not accept the technology of Cash Delivery as a payment method. The author uses a quantitative methodology to gather primary data from 200 respondents in many major cities where the COD campaign operates. The results demonstrate that perceptions of usefulness, usability, and attitude contribute to consumers' intentions to utilize the COD payment method. Trust was discovered to be a significant determinant of consumers' desire to use the COD payment option. The implementation of COD should be more successful if the reasons mentioned are taken into account.